Differentiating the relationships between traditional and new media use and sleep quality during the COVID-19 pandemic: roles of psychological distress and age - Xu, Tong; Zhu, Dongmei; Yu, Zhaoliang; Dang, Junhua; Schiöth, Helgi (Frontiers in Psychology, 2024)
Background: Numerous studies have consistently demonstrated a decline in sleep quality during the COVID-19 pandemic. The primary objective of this study is to explore the impact of engaging with pertinent epidemic information through the media amid the COVID-19 crisis on individuals' sleep quality and the underlying mechanisms through which this influence operates.Methods: An online cross-sectional study design was employed. A total of 1,063 British adults (36.2% males; Mage = 38.85, SDage = 13.36, ranging from 18 to 77 years old) participated in the study and completed our questionnaires, which included media usage frequency during the pandemic, the 10-item Kessler Psychological Distress Scale (K10), the Insomnia Severity Index (ISI), and the Tenitem Personality Inventory (TIPI).Results: Pearson's correlation analyses indicated that there was no significant correlation between COVID-19-related traditional media use (television, radio, newspaper) and psychological distress or sleep quality. However, exposure to information related to COVID-19 through new media use (Facebook, Tik Tok, Twitter) was correlated with greater psychological distress and poorer sleep quality. A moderated mediation analysis showed that psychological distress fully mediated the relationship between new media use and poor sleep, which was moderated by age, with the association between psychological distress and poor sleep quality being stronger among older adults.Exposure to information of COVID-19 via new (but not traditional) media use deteriorated sleep quality through greater psychological distress, and this relationship was stronger among older adults.